THE TREND OF DEVELOPMENT OF SUFI TEACHINGS IN INDIA (Scientific journal of the Fergana State University, 2026)
This article provides an in-depth analysis of the stages of formation and development of Sufi teachings in the territory of India. When the representatives of Sufism arrived in this land, they adapted to the lifestyle of the local population and engaged in direct interaction with them. As a result, the views of the Sufis, which were based on morality, spiritual purity, and divine love, spread rapidly among Indian society. Moreover, since these ideas shared certain commonalities with the religious and spiritual outlook of the local people, the Sufis found it relatively easy to attract individuals inclined towards their path. In the history of Sufism in India, four Sufi orders occupied a particularly significant place: the Chishti, Qadiri, Suhrawardi, and Naqshbandi. These orders exerted a considerable influence not only in religious and spiritual guidance but also in the broader social life of the community.